2003
DOI: 10.4049/jimmunol.171.1.159
|View full text |Cite
|
Sign up to set email alerts
|

CC Chemokine Receptor 9 Expression Defines a Subset of Peripheral Blood Lymphocytes with Mucosal T Cell Phenotype and Th1 or T-Regulatory 1 Cytokine Profile

Abstract: The chemokine receptor CCR9 is expressed on most small intestinal lamina propria and intraepithelial lymphocytes and on a small subset of peripheral blood lymphocytes. CCR9-expressing lymphocytes may play an important role in small bowel immunity and inflammation. We studied the phenotype and functional characteristics of CCR9+ lymphocytes in blood from normal donors. A subset of CCR9+ T cells have a phenotype of activated cells and constitutively express the costimulatory molecules CD40L and OX-40. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
83
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 55 publications
11
83
0
1
Order By: Relevance
“…These data suggest the potential involvement of CCR9 ϩ T cells in the pathogenesis of SB CD (11). Furthermore, we have demonstrated that the memory subset of circulating CCR9 ϩ CD4 ϩ T cells in healthy donors has characteristics of mucosal T lymphocytes since they have an activated phenotype, respond to anti-CD2 stimulation, and exhibit a Th1 or T regulatory 1 cytokine profiles (12).…”
mentioning
confidence: 61%
See 4 more Smart Citations
“…These data suggest the potential involvement of CCR9 ϩ T cells in the pathogenesis of SB CD (11). Furthermore, we have demonstrated that the memory subset of circulating CCR9 ϩ CD4 ϩ T cells in healthy donors has characteristics of mucosal T lymphocytes since they have an activated phenotype, respond to anti-CD2 stimulation, and exhibit a Th1 or T regulatory 1 cytokine profiles (12).…”
mentioning
confidence: 61%
“…The combined expression of ␣ 4 ␤ 7 /CCR9 by intestinal homing T lymphocytes may further define SB vs colonic mucosal T cell trafficking through CCL25 (selectively expressed in the SB) triggering of integrin activation from CCR9 engagement (9,10). Therefore, expression of CCR9 by mucosal homing T cells may be used to distinguish SB from colonic immune responses (12). CCL25 is selectively expressed in the thymus and SB endothelial cells, intestinal crypts, and a subset of LP cells (9,10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations